2005
DOI: 10.1111/j.1365-2745.2005.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene diversity in a fragmented population of Briza media: grassland continuity in a landscape context

Abstract: Summary1 We investigated patterns of allozyme variation in demes of the grass Briza media in semi-natural grassland fragments within a mosaic agricultural landscape on the Baltic island of Öland. In the study area, Briza is both a characteristic species of old pastures and an early colonizer of young grasslands developing on previously forested or arable sites. 2 Generalized linear models revealed that descriptors of both present landscape structure and past grassland history are significant determinants of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 54 publications
(47 reference statements)
3
50
3
Order By: Relevance
“…Several studies have shown that habitat variation and management intensity can impact genetic variation. Prentice and coworkers described significant associations between allozyme frequencies and grassland habitat variation in the grasses Festuca ovina (Prentice et al 1995) and Briza media (Prentice et al 2006). In addition, Magda et al (2004) showed that mowing juvenile R. minor can drastically reduce population density the following year and the population may even become extinct within 3 years.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that habitat variation and management intensity can impact genetic variation. Prentice and coworkers described significant associations between allozyme frequencies and grassland habitat variation in the grasses Festuca ovina (Prentice et al 1995) and Briza media (Prentice et al 2006). In addition, Magda et al (2004) showed that mowing juvenile R. minor can drastically reduce population density the following year and the population may even become extinct within 3 years.…”
Section: Discussionmentioning
confidence: 97%
“…The Jordtorp area (56°33 0 58 00 N, 16°33 0 58E) is located on the Baltic Island of Ö land (Sweden) and covers an area of 4.5 9 4.5 km with an overall flat topography (Prentice et al 2006;Johansson et al 2008;Reitalu et al 2008). The present landscape is characterized by a mosaic of arable fields, deciduous forest and grasslands.…”
Section: Study Areamentioning
confidence: 99%
“…Studies using marker genes reveal that some grassland species show clear evidence of genetic drift as a result of population fragmentation (e.g., van Treuren et al 1994;Luijten et al 2000;van Rossum et al 2004;Helm et al 2009), while other studies show low levels of differentiation between fragmented populations (e.g., Weidema et al 2000;Honnay et al 2006). Prentice et al (2006) used allozyme data from the outcrossing, perennial grass Briza media to explore the association between genetic diversity and various descriptors of landscape structure and land-use history in a fragmented grassland landscape on the Baltic island of Ö land (SE Sweden). The present-day habitat connectivity was significantly associated with the level of gene diversity within demes (i.e.…”
Section: Introductionmentioning
confidence: 97%